Dynamic near-infrared optical imaging of 2-deoxyglucose uptake by intracranial glioma of athymic mice. - Heling Zhou (PLoS ONE, 2009)
It is recognized that cancer cells exhibit highly elevated glucose metabolism compared to non-tumor cells. We have applied in vivo optical imaging to study dynamic uptake of a near-infrared dye-labeled glucose analogue, 2-deoxyglucose (2-DG) by orthotopic glioma in a mouse model.The orthotopic glioma model was established by surgically implanting U87-luc glioma cells into the right caudal nuclear area of nude mice. Intracranial tumor growth was monitored longitudinally by bioluminescence imaging and MRI. When tumor size reached >4 mm diameter, dynamic fluorescence imaging was performed after an injection of the NIR labeled 2-DG, IRDye800CW 2-DG. Real-time whole body images acquired immediately after i.v. infusion clearly visualized the near-infrared dye circulating into various internal organs sequentially. Dynamic fluorescence imaging revealed significantly higher signal intensity in the tumor side of the brain than the contralateral normal brain 24 h after injection (tumor/normal ratio, TNR = 2.8+/-0.7). Even stronger contrast was achieved by removing the scalp (TNR = 3.7+/-1.1) and skull (TNR = 4.2+/-1.1) of the mice. In contrast, a control dye, IRDye800CW carboxylate, showed little difference (1.1+/-0.2). Ex vivo fluorescence imaging performed on ultrathin cryosections (20 microm) of tumor bearing whole brain revealed distinct tumor margins. Microscopic imaging identified cytoplasmic locations of the 2-DG dye in tumor cells.Our results suggest that the near-infrared dye labeled 2-DG may serve as a useful fluorescence imaging probe to noninvasively assess intracranial tumor burden in preclinical animal models.